Semarak Ramadhan with IPSis: preparation and give away bubur lambuk to campus community - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
In the spirit of giving during Ramadhan, IPSis took an opportunity to prepare “bubur lambuk” (a mildly spiced porridge) for the campus community. IPSis staff were actively involved in cooking and packing as well as distributing packs of “bubur lambuk” for the community to enjoy. The cook, En. Badle Shah Yahaya assisted the staff in preparing bubur lambuk starting from 7.30 am and was completed at 12.00 noon. The purpose of this activity is all about creating special and meaningful bonding moments among IPSis staff and the campus community. The activity ended with an iftar gathering of IPSis staff at Dewan Agong Tuanku Canselor Multilevel Parking area.